HUMAN FACTORS ANALYSIS AND CLASSIFICATION SYSTEM (HFACS) MODEL IN ANALYZING CONSTRUCTION ACCIDENTS - Santika Sari; Akhmad Nidhomuz Zaman; Mohammad Rachman Waluyo; Nurfajriah Nurfajriah (Spektrum Industri, 2020)
Industrialization development, which is being implemented in some areas, is increasing rapidly. There are over one hundred thousand construction companies in Indonesia. Thus, the risk of accidents in the construction field is also likely to increase. Moreover, Indonesia is one of the countries with the highest construction accidents according to ASEAN's accident rate. This will cost a significant loss. The Indonesian construction industry should conduct a more in-depth investigation into the problem so that improvements would significantly decrease the accident rate. This research aims to obtain the first modification of HFACS models to be implemented in the companies. Thus, it is expected that there is a correction to the dominant factor. HFACS model is an accident investigation method based on the human error factor. This research is generally divided into three steps. There are preliminary, data collecting, then conclusion and recommendation. Based on the explanation above, it is obtained that the development of the HFACS model is by adding the level of an external factor, which obtained 1,2% in the construction industry. Through the recommendation based on the result of this research, be expected that construction companies in Indonesia could make continuous improvements to reduce the accident